Family Values in Domee Shi Movie Turning Red - Bahri, Syamsul; Melinda, Putri; Nasution, Ananta Thoriq Arrazi (Proceeding International Conference on Malay Identity, 2024)
In the Pixar film "Turning Red," family serves as a crucial vessel for transmitting culture and ideology, particularly evident in the Chinese family dynamics portrayed within a modern Canadian society. This observation aligns with the premise that families are fundamental in shaping individuals' beliefs and values. This study explores the family dynamics depicted in the Pixar film "Turning Red" by applying Van Wel's (1994) theory of family bonding and Pecchioni and Nussbaum's (2001) theory of family conflict. The objective is to gain a nuanced understanding of how these theories illuminate the complex relationship between Mei, a thirteen-year-old protagonist experiencing a magical panda transformation, and her overprotective mother, Ming. A qualitative methodology is employed, analyzing scenes from the movie that exemplify bonding and conflictual behaviors. As findings, there are seven bonding values that found in this movie, namely attachment, commitment, interdependence, closeness, trust, intimacy, and love. Conflict values are also found that consist of five aspects. This study contributes to the understanding of family relationships in media by demonstrating how family bonding and conflict theories can be applied to analyze the intricacies of parent- child interactions.